The intraoperative portable CT scanner-based spinal navigation: a viable option for instrumentation in the region of cervico-thoracic junction - Barsa, Pavel; Frőhlich, Robert; Šercl, Miroslav; Buchvald, Pavel; Suchomel, Petr (European spine journal, 2016)
PURPOSE: Innovative intraoperative imaging modalities open new horizons to more precise image acquisition and possibly to better results of spinal navigation. Planning of screw entry points and trajectories in this prospective study had been based on intraoperative imaging obtained by a portable 32-slice CT scanner. The authors evaluated accuracy and safety of this novel approach in the initial series of 18 instrumented surgeries in anatomically complex segment of cervico-thoracic junction. METHODS: We report on the single-institution results of assessment of anatomical accuracy of C5-T3 pedicle screw insertion as well as its clinical safety. The evaluation of total radiation dose and of time demands was secondary endpoint of the study. RESULTS: Out of 129 pedicle screws inserted in the segment of C5-T3, only 5 screws (3.9 %) did not meet the criteria for correct implant positioning. These screw misplacements had not been complicated by neural, vascular or visceral injury and surgeon was not forced to change the position intraoperatively or during the postoperative period. Quality of intraoperative CT imaging sufficient for navigation was obtained at all spinal segments regardless of patient´s habitus, positioning or comorbidity. A higher radiation exposition of the patient and 27 min longer operative time are consequences of this technique. CONCLUSIONS: The intraoperative portable CT scanner-based spinal navigation is a reliable and safe method of pedicle screw insertion in cervico-thoracic junction.
Keywords: Cervical Vertebrae; krční obratle; Pedicle Screws; Tomography, X-Ray Computed; počítačová rentgenová tomografie; Prospective Studies; lidé; chirurgie s pomocí počítače; Surgery, Computer-Assisted; Orthopedic Procedures; Thoracic Vertebrae; Humans; ortopedické výkony; pedikulární šrouby; hrudní obratle; prospektivní studie